Fashion communication: a way to change comsumption behaviour towards ethical fashion - Cohen, Nathalie (2015)
In view of the major social and environmental problems, with which we are faced nowadays, we noticed a certain absence of values in society, where man draws many more resources than nature can replace in the short or medium term. Within the framework of fashion emerges the ethical fashion as a movement in this direction, intending to change this current paradigm. Ethical fashion encompasses different concepts such as fair trade, sustainability, working conditions, raw materials, social responsibility and the protection of animals. This study aims to determine which type of communication are fashion brands using in this context, and if this communication aims at educating the consumer for a more ethical consumer behavior. For this study were selected 44 fashion brands associated with the Ethical Trade Initiative. The method used for the research development was content analysis for which first was made a data collection of the information provided on the websites and social networks of the selected fashion brands. The data was analyzed taking into account the quality and type of information published related to ethical fashion, for which an ordinal scale was created as a way of measuring and comparing results.